Consideration of The Judge of The State Court of Surabaya in The Crime Of Racism - Evi Yufita; Zainal Arifin; Mahfud Fahrazi (UNISKA LAW REVIEW, 2022)
This study discusses the judge's considerations and progressive law in court decisions against defendants for racism crimes. Judges in their considerations and decisions have not fulfilled the aspects of justice and expediency. The purpose of this study is to analyze the judgments of the Surabaya District Court judges in imposing a sentence on the perpetrators of the crime of racism in the decision number 3147/Pid.Sus/2019/PNSby and to analyze the decision number 3147/Pid.Sus/2019/PNSby in terms of progressive legal theory. The method used in this research is normative juridical. The results of this study are the judge's consideration of the case decision number 3147/Pid.Sus2019/PNSby disagrees with the judge's considerations regarding the criminal conviction given to Syamsul Arifin as a defendant in a criminal act of racism. Based on the facts, Syamsul Arifin was proven guilty and one of the evidences was the circulation of a video stating that the defendant deliberately used the word "monkey" aimed at Papuan students at the Jl. Kalasan No. 10 cities of Surabaya. The impact of the circulation of the video was a wave of demonstrations or demonstrations that occurred in various cities such as Jayapura, Sorong and Manokwari, resulting in the mass burning of the Manokwari City DPRD building. The riots that occurred had bad consequences because they threatened national security. The judge's decision in this case will be of no benefit to the community, especially the Papuan people, because the sentences given to the defendants are light and short. The application of sanctions can be categorized as less effective and this judge's decision does not meet the progressive legal theory because it has not fully met the values of certainty, justice and expediency. The judge should have considered the consequences of the defendant's actions that created national tension, resulting in many riots in various parts of the Indonesian state.